2019
DOI: 10.4103/jfmpc.jfmpc_23_19
|View full text |Cite
|
Sign up to set email alerts
|

Treatment compliance among previously diagnosed type 2 diabetics in a rural area in Southern India

Abstract: Background: Treatment adherence will help to achieve good glycemic control among diabetics and will lead to lesser complications associated with the disease. This study was carried out to determine the compliance to treatment among previously diagnosed diabetic patient and their level of glycemic control, in a rural area. Materials and Methods: This cross-sectional study was conducted among all previously diagnosed diabetics above 30 years, on treatment for more than 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Glycemic control was achieved among 58. Forty-five percentage of study participants despite higher compliance reported in this study, and a similar result was observed in other studies done by Pattanaik et al [15] and Muliyil et al [16]. There was no significant association of appointment (p value, 0.386), treatment (p value, 0.875), and diet (p value, 0.674) compliance with glycemic control in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Glycemic control was achieved among 58. Forty-five percentage of study participants despite higher compliance reported in this study, and a similar result was observed in other studies done by Pattanaik et al [15] and Muliyil et al [16]. There was no significant association of appointment (p value, 0.386), treatment (p value, 0.875), and diet (p value, 0.674) compliance with glycemic control in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Studies done in rural Ludhiana by Bansal et al [13] and in urban Puducherry by Santhanakrishnan et al [14] also reported higher compliance (82.5% and 76%, respectively) in T2DM patients. Some studies from the southern part of India reported compliance in the range of 52–64% [15]. Reasons for higher compliance in this study were individualized care, education and training of patients, and monitoring of treatment and follow-up well maintained at this private diabetic clinic.…”
Section: Discussionmentioning
confidence: 63%
“…There was a rapid increase in knowledge about Diabetes, as experimental group members received information regarding different aspects of Diabetes during each session of the therapy, which they were expected to apply. Despite higher compliance reported in this study limited improvement in glycemic control was achieved, and a similar result was observed in other studies 35,36 Reinforcing self-care with diabetes education for patients who have not met glycemic targets helps improve A1C and could be considered as a necessary component of ongoing diabetes care 37 .…”
Section: Effectiveness Of Cognitive Behavioral Nursing Intervention O...supporting
confidence: 82%
“…Research conducted in rural Ludhiana by Bansal et al 32 and in urban Puducherry by Santhanakrishnan et al 33 also found high adherence rates of 82.5% and 76% among type 2 diabetes mellitus (T2DM) patients. Some studies from southern India reported adherence rates between 52% and 64% 34 . Factors contributing to the higher adherence rates in this study included personalized care, patient education and training, and ongoing treatment monitoring and followup.…”
Section: Effectiveness Of Cognitive Behavioral Nursing Intervention O...mentioning
confidence: 99%